Correction and development of psychomotor function of deaf children of midchildhood by facilities of mobile games. - Іvahnenko A.A (Kharkov National Pedagogical University, 2011)
The problem of correction and development of psychomotor sphere of deaf children of midchildhood is considered by facilities of physical education, in particular by mobile games. The analysis of publications of research workers is resulted in relation to the problem of development of psychomotor function of deaf children in a theory and practice of correction work. In theory is grounded value of mobile games as effective mean of development of psychomotor sphere of deaf lower boys. The necessity of application of the specially adapted mobile games is set in the process of correction-pedagogical work with the deaf children of midchildhood. The pedagogical looking is presented after the features of playing activity of deaf children of 1-4 classes.